On the calculation of prospective and retrospective reserves in non-Markov models - Marcus C. Christiansen (European Actuarial Journal, 2021)
Almost all life and health insurance models in the actuarial literature use either a Markov assumption or a semi-Markov assumption. This paper shows that non-Markov modelling is also feasible and presents suitable numerical and statistical tools for the calculation of prospective and retrospective reserves. A central idea is to base the calculation of reserves on forward and backward transition rates. Feasible estimators for the forward transition rates have been recently suggested in the medical statistics literature. This paper slightly extends them according to insurance needs and newly introduces symmetric estimators for backward transition rates. Only few adjustments are actually needed in the classical insurance formulas when switching from Markov modelling to as-if-Markov evaluations in order to avoid model risk.
Keywords: 510; Life and health insurance; Semi-Markov model; Kolmogorov forward equation; Landmark Aalen–Nelson estimator; Landmark Aalen–Johansen estimator